1973
DOI: 10.1159/000231077
|View full text |Cite
|
Sign up to set email alerts
|

Reaginic Antibody Formation in Mice Injected with Rabbit Anti-Mouse Thymocyte Serum

Abstract: A new model system for inducing reaginic antibody formation in mice is presented, namely a single injection of rabbit anti-mouse thymocyte serum (RAMTS). Using this model we have shown that X-irradiation (450 rad) administered to CBA mice 24 h after a single injection of RAMTS or IgG- (RAMTS) results in a sustained moderately high level of reagins against rabbit serum proteins with a concomitant barely detectable level (titer 1:5) of γ1-antibodies. Splenectomy and thymectomy had no demonstrable effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1975
1975
1983
1983

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It has been reported that the carrier-specific helper cells for the IgE and IgG 1 antibody response are different (20,50). Since atrophy of the spleen was already severe 5 days after injection of DNT (47) the results obtained indicate, as has been shown in splenectomized animals (19,29,39,50), that the spleen may not be an important organ in the production of IgE but is important in the production of IgG1. When DNT was inactivated by heat, it no longer had any effect on the spleen or on the adjuvanticity of pertussigen (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…It has been reported that the carrier-specific helper cells for the IgE and IgG 1 antibody response are different (20,50). Since atrophy of the spleen was already severe 5 days after injection of DNT (47) the results obtained indicate, as has been shown in splenectomized animals (19,29,39,50), that the spleen may not be an important organ in the production of IgE but is important in the production of IgG1. When DNT was inactivated by heat, it no longer had any effect on the spleen or on the adjuvanticity of pertussigen (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…This lack of correlation of animal models with the allergic state in man was overcome with the demonstration by Levine and coworkers that persistent and boosterable IgE antibodies can be stim ulated in certain strains of mice by injection of low doses of antigen plus Al(OH)3 [17,18,49,50]. Following the report of these observations, oth er experimental manipulations have been reported that lead to enhanced IgE synthesis [7,14,23,28,29,31,36,[45][46][47], One such method, the use of whole cells or extracts containing the HSF of B. pertussis, has shown that persistent and boosterable titers of reaginic antibody can be obtained with high doses of antigen and adjuvant, and this response dif fers from that obtained with antigen and Al(OH), [23], These findings are extended in the present investigation. It was observed that although both AI(OH)3 and HSF stimulate hemagglutinin and reagin, Al(OH)3 usually is a better stimulator of the former while HSF is of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the Al(OH)3-induced stimulation of IgE antibody pro duction described by Levine and coworkers, other methods of augment ing IgE antibody production to a particular antigen have been described [7,14,23,24,28,29,31,36,[45][46][47]. We have recently investigated one such method, that is the enhancement of specific IgE production to an an tigen by treatment of mice with extracts of the histamine-sensitizing factor (HSF) of Bordetella pertussis [23].…”
Section: Introductionmentioning
confidence: 99%
“…Since concanavalin A (Con A) is a potent T cell mitogen, and both in hibits and enhances the formation of non-IgE antibodies in vivo [5,7,13] and in vitro [3,20,22,26], it was decided to investigate the effect of Con A on reaginic antibody formation in mice. We had previously shown that rabbit antimouse thymocyte serum (RAMTS) induced the formation of reagins in mice to serum proteins present in RAMTS [11],…”
Section: Introductionmentioning
confidence: 99%